HUBUNGAN ANTARA KARAKTERISTIK, TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA TERHADAP PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS SIANTAN HULU KECAMATAN PONTIANAK UTARA TAHUN 2014 - ., Fitri Yulianti (Jurnal Mahasiswa PSPD FK Universitas Tanjungpura, 2014)
Background: Exclusive breastfeeding (EBF) means that the infantreceives only breast milk for the first six months of life after birth.Puskesmas Siantan Hulu has the lowest EBF rate (11,76%) in PontianakCity. Characteristic, knowledge and family support are suggested toinfluence EBF. Objective: Determining the relationship of thecharacteristic, knowledge and the family support with the practice of EBF.Methodology: This study was cross sectional analytic approach. Thisresearch was conducted at September 2013 to July 2014. Subjects weremothers who having children aged 0–6 months. Total sample was 86respondents. Data was analyzed by chi-square test. Results: This studyshowed that 81,40% respondents had 20-35 years of age, 58,14%respondents had primary education, 48,84% respondents with primipara,48,84% respondents had a low knowledge, 52,33% respondents withgood family support and 56,98% respondents practiced EBF. There wereno relationship between age (p=0.081) and mother’s employment status(p=0.927) with practice EBF. There were relationship among education(p=0,046), status of parity (p=0,008), mother’s knowledge (p=0.000) andfamily support (p=0.004) with the practice of EBF. Conclusion: Education,status of parity, mother’s knowledge and family support have relationshipwith the practice of EBF.Keywords : Exclusive breastfeeding, knowledge, family support. 1. Medical Education Program, Fakultas Kedokteran UniversitasTanjungpura, Pontianak, KalimantanBarat. 2. Department of Public Health, Fakultas Kedokteran UniversitasTanjungpura, Pontianak Kalimantan Barat. 3. Department of Histology, Fakultas Kedokteran UniversitasTanjungpura, Pontianak, Kalimantan Barat.